Powering The World With Hydrogen - Theresia Asteria (Budapest International Research and Critics University, 2018)
The global energy consumption has been on the rise worldwide as developing nations begin to industrialize and as consumers in developed nations buy more energy consuming appliances to make life more comfort- able. If the current trends continue, we may face an energy shortage in future. The phrase